Site-Specific Multilevel Modeling of Potato Response to Nitrogen Fertilization - Parent, Serge-Étienne; Leblanc, Michaël A.; Parent, Annie-Claude; Coulibali, Zonlehoua; Parent, Léon E. (Frontiers in Environmental Science, 2017)
Technologies of precision agriculture, digital soil maps and meteorological stations provide a minimum data set to guide precision farming operations. However, determining optimal nutrient requirements for potato (Solanum tuberosum L.) crops at subfield scale remains a challenge given specific climatic, edaphic and managerial conditions. Multilevel modeling can generalize yield response to fertilizer additions using data easily accessible to growers. Our objective was to elaborate a multilevel N fertilizer response model for potato crops using the Mitscherlich equation and a core data set of 93 N fertilizer trials conducted in Quebec, Canada. Daily climatic data were collected at 10 km □□ 10 km resolution. Soils were characterized by organic matter content, pH and texture in the arable layer, and by texture and tools of pedometrics across a gleization-podzolization continuum in subsoil layers. There were five categories of preceding crops and five cultivar maturity orders. The three Mitscherlich parameters (Asymptote, Rate and Environment) were most often site-specific. Sensitivity analysis showed that optimum N dosage increased with non-leguminous high-residue preceding crops, coarser soils, podzolization, drier climatic condition and late cultivar maturity. The inferential model could guide site-specific N fertilization using an accessible minimum data set to support fertilization decisions. As decision-support system, the model could also provide a range of optimum N doses across a large spectrum of site-specific conditions including climate change.